Mathematics Games Creation by Using Block-Based Programming (Scratch) to Enhance Students Learning Experiences - Fauzi, Ahmad; Syafi’i, Mohamad; Musthofa, Syarto; Wandira, Raju; Azmi, Zain; Zikri, Muhamad (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
The use of information technology in making teaching materials by teachers can improve students' learning experiences. One of learning methods that can be adopted with technology integration is game-based learning design. The problem is that teachers generally lack the ability to utilize technology in learning process. Through this service activity, the team provides assistance to teachers at MTsN 5 and MTsN 6 Padang in designing interesting learning process using game-based learning design. This approach produces active involvement of students in the learning process while increasing students' creativity and understanding.